Tricarbonylrhenium(I) complexes with the N, 6-dimethylpyridine-2-carbothioamide ligand: combined experimental and calculation studies. Issue 14 (18th July 2018) - Lyczko, Krzysztof; Lyczko, Monika; Meczynska-Wielgosz, Sylwia; Kruszewski, Marcin; Mieczkowski, Józef
Abstract: A new series of tricarbonyl complexes of rhenium(I) in the "2 + 1" system with the bidentate ligand N, 6-dimethylpyridine-2-carbothioamide ((CH3 )NC5 H4 -CS-NH-CH3, MeLH (Me) NS ) and a monodentate ligand (halides Cl, Br, or I, and the pseudohalide NCS anion) was synthesized. The use of mixed ligands led to the formation of neutral tricarbonylrhenium(I) complexes [Re(CO)3 (MeLH (Me) NS )X] (X = Cl, Br, I, NCS) (1 –4 ). Single-crystal X-ray diffraction was used to determine the crystal structures of all four compounds and those results were compared with molecular structures obtained from DFT calculations using the PBE0/def2-TZVPD approach. The complexes were also characterized by spectroscopic (FT-IR, NMR, and UV–vis) and analytical (HPLC, TGA, EA, ESI-MS) techniques. IR and UV–vis spectra were also calculated by DFT and TD-DFT methods. The cytotoxicity of these complexes was estimated using human ovarian cancer cell lines (A2780 and A2780cis), cervical cancer cells (HeLa), and non-cancerous human embryonic kidney cells (Hek-293). The toxicity of most complexes was moderate or low toward cancer cell lines (IC50  = 46–231 μM) and similar against non-cancerous cells (IC50  = 41-121 μM). Only the complex with chlorido ligand remarkably inhibited growth of ovarian cancer cells (IC50  = 3 and 12 μM for A2780 and A2780cis, respectively). The cytotoxicity of1 was higher than that of cisplatin. Abstract :